Cornelia de lange manifestations in otolaryngology: A systematic review and meta‐analysis. (13th July 2019) - Bergeron, Mathieu; Chang, Katherine; Ishman, Stacey L.
Abstract : Objectives: Cornelia de Lange syndrome (CdLS) is a rare genetic disorder. Our goal was to systematically review the literature regarding otolaryngology manifestations of CdLS. Methods: We systematically reviewed the PubMed, Embase, CINAHL, Scopus, and Google Scholar databases for original articles of otolaryngology manifestations for patients with CdLS. These articles were analyzed, and pooled prevalence was calculated. Results: We analyzed 1, 310 patients included in 35 case series and 34 case reports. Hearing loss was present for many patients (27 studies), with sensorineural hearing loss affecting 40.3% (95% confidence interval [CI]: 17.3–63.4) and conductive affecting 22.7% (95% CI: 5.7–39.7). Recurrent acute otitis media was the most frequent infectious manifestation, with 56.5% (95% CI: 34.1–78.4) in seven studies, followed by recurrent airway infections with 44.1% (95% CI: 11.0–87.1) in five studies. Forty‐nine (49.7%) percent of patients (95% CI: 25.9–73.6) in nine studies had dysphagia, and 76.6% (95% CI: 59.8–93.3) in four studies had some degree of dysphonia. Craniofacial anomalies were reported in 30 studies, with micrognathia (53.1%; 95% CI: 34.1–72.1) and high arched palate (70.6%; 95% CI: 56.5–84.8) commonly reported. Additional physical exam abnormalities reported included those involving: lips (76.8%; 95% CI: 65.3–88.4), dentition (65.1%; 95% CI: 27.2–100), mouth (85.5%; 95% CI: 76.2–93.8), and eyelashes (87.1%; 95% CI: 77.2–96.9). Sleep‐disordered breathing or obstructive sleep apnea affected 25.8% (95% CI: 11.4–40.2) of patients (7 studies). Airway anomalies were reported in 11 case reports. Conclusion: This is the first comprehensive evaluation of otolaryngologic manifestations in the CdLS literature. Most reported hearing loss and craniofacial anomalies. Sleep disorders occurred in a minority of patients, whereas airway disorders were primarily reported in case reports. These conditions should be further examined given their potential life‐threatening implications. Level of Evidence: 3a Laryngoscope, 130:E122–E133, 2020